2015
DOI: 10.1158/1078-0432.ccr-14-0432
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Analysis Identifies Novel Subtypes and Targets of Triple-Negative Breast Cancer

Abstract: Purpose Genomic profiling studies suggest triple-negative breast cancer (TNBC) is a heterogeneous disease. In this study we sought to define TNBC subtypes and identify subtype-specific markers and targets. Patients and Methods RNA and DNA profiling analyses were conducted on 198 TNBC tumors (ER-negativity defined as Allred Scale value ≤2) with >50% cellularity (discovery set: n=84; validation set: n=114) collected at Baylor College of Medicine. An external data set of 7 publically-accessible TNBC studies was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
1,077
2
24

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,069 publications
(1,148 citation statements)
references
References 33 publications
45
1,077
2
24
Order By: Relevance
“…Burstein et al 25 identified four different TNBC subtypes (LAR, MES, BLIS, BLIA) with the identification of similar pathways and a prognostic value for the BLIA subgroup similar to that for the signature identified in our study. This subgroup displays an upregulation of B-cell, T-cell, and natural killer cell immune-regulating pathways and an activation of STAT transcription factor-mediated pathways.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Burstein et al 25 identified four different TNBC subtypes (LAR, MES, BLIS, BLIA) with the identification of similar pathways and a prognostic value for the BLIA subgroup similar to that for the signature identified in our study. This subgroup displays an upregulation of B-cell, T-cell, and natural killer cell immune-regulating pathways and an activation of STAT transcription factor-mediated pathways.…”
Section: Discussionsupporting
confidence: 78%
“…The two immune modules identified in this study had many biological connections with other eight immune prognosis signatures published for TNBC. [18][19][20][21][22][23][24][25] Neoadjuvant chemotherapy is increasingly being used for TNBC, because these tumors have a poor prognosis, are assumed to be chemosensitive and no alternative specific systemic treatment is available. Patients with a complete pathologic response (pCR) after neoadjuvant chemotherapy have a better outcome than those with residual disease, and pCR is a good surrogate for long-term survival and cure in this specific subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UNC dataset classified its 855 tumours into the five intrinsic PAM50 molecular subtypes and further sub-divided the basal-like and normal-like subtypes into claudin-low tumours, basal-like (basal, 140), claudin-low (C-Low, 90), HER2-enriched (HER2, 144), luminal A (LumA, 243), luminal B (LumB, 162) and normal-like (N-Like, 76). Triple-negative breast cancers (TNBCs) from the UNC cohort [based on immunohistochemistry (IHC) of the oestrogen (ER) and progesterone receptors (PR) and HER2] were assigned a TNBC subtype based on the expression of subtype-specific gene signatures (Burstein et al, 2015). This analysis classified the 200 TNBCs into 83 basal-like immune-activated (BLIA), 95 basal-like immune-suppressed (BLIS), 6 luminal androgen receptor (LAR) and 16 mesenchymal (MES).…”
Section: Analysis Of Trpc1 Expression In Breast Tumoursmentioning
confidence: 99%
“…Subtype 3 is Basal-like immune suppressed (BLIS) which involves down regulation of pathways relating to the function of immune cell regulatory pathways. Lastly, subtype 4 Basal-like immune activated (BLIA) shows the up regulation of pathways relating to immune cell function [34]. The (LAR) and (MES) subtypes overlap with Lehmann and colleagues while the (BLIS) and (BLIA) take from the other four types.…”
Section: Genetic Subtyping Of Tnbcmentioning
confidence: 95%